Evaluasi Moralitas Berdasarkan Estetika Desain Karakter pada Gim Baldur’s Gate 3 - Muhammad Adharamadinka; Irfan Dwi Rahadianto; Tiara Radinska Deanda (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2025)
Characters in games play a crucial role in enhancing gameplay appeal, such as in Baldur's Gate 3, a role-playing game (RPG) that allows players to shape the story through moral choices. Each character has a unique setting in a fantasy world, and the player's morality is reflected in the decisions they make. This study aims to determine players' moral impressions of character design aesthetics using Moral Foundation Theory (MFT). The method used was a kuesioner with 52 game player respondents, who were given visual stimuli in the form of two-dimensional character images. Respondents were asked to answer an MFT-based questionnaire and provide spontaneous word associations to the characters depicted. The results of factor and association analyses indicate that visual elements such as costumes, facial expressions, and accessories significantly influence the formation of moral impressions. The Fairness/Cheating foundation was the most dominant in perceptions of the characters Astarion, Karlach, Gale, and Wyll. Strong character visualizations also create an emotional atmosphere and increase players' narrative engagement. This study demonstrates that character visual aesthetics can influence players' ethical perceptions and support moral narratives in games, contributing to the development of value-based character design in the gaming industry.